2017
DOI: 10.4103/ijc.ijc_251_17
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice toward cervical cancer among women attending Obstetrics and Gynecology Department: A cross-sectional, hospital-based survey in South India

Abstract: Although women are having good knowledge, positive attitude toward cervical cancer screening and prevention still there is a gap to transform it into practice. There is a need for more educational programs to connect identified knowledge slits and uplift of regular practice of cervical cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
80
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 9 publications
15
80
10
1
Order By: Relevance
“…6 Among the studies conducted abroad, Touch et al reported 74%, Shrestha et al reported 65.7% and Tran NT et al reported more than 60% having heard of the disease in Combodia, Nepal and Korea respectively. [7][8][9] In the current study , friends and relatives followed by media were the main information sources for the respondents and these results are in agreement with those reported by Narayana et al and Abdullahi et al 5,10 More than 80% of the respondents were aware that cervical cancer was preventable and about the availability of screening test for the disease. Tran et al reported that only 36% of the respondents knew that cancer cervix could be prevented.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…6 Among the studies conducted abroad, Touch et al reported 74%, Shrestha et al reported 65.7% and Tran NT et al reported more than 60% having heard of the disease in Combodia, Nepal and Korea respectively. [7][8][9] In the current study , friends and relatives followed by media were the main information sources for the respondents and these results are in agreement with those reported by Narayana et al and Abdullahi et al 5,10 More than 80% of the respondents were aware that cervical cancer was preventable and about the availability of screening test for the disease. Tran et al reported that only 36% of the respondents knew that cancer cervix could be prevented.…”
Section: Discussionsupporting
confidence: 90%
“…The results revealed that 91.56% had heard of cervical cancer and these are higher than reported by Narayana et al 5 Since the present study was conducted in a tertiary care teaching hospital where women are able to assess better information, could be the major reason for large proportion of women having heard of cervical cancer. Also the proportion of urban respondents was higher which may be another reason for these results.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Points to, aware about thyroid gland location (1 point), de inition of hypothyroidism (1 point), symptoms of hypothyroidism (1 point for any four correct responses among symptoms like Hair fall, Neck pain, neck swelling, sore throat, constipation, weight gain, menstrual irregularities, infertility, and lethargy), major causes of hypothyroidism (1 point for any four correct responses among causes like lack of iodine in diet, damage or disorders of pituitary gland, thyroid surgery, radiation therapy, genetic dysfunction, auto-immunity against thyroid gland, treatment of hyperthyroidism, and certain medications), population at risk (1 point for any four correct responses among female, elderly people, pregnant women, family history of hypothyroidism, and obese person), curability of hypothyroidism (1 point), hypothyroidism affects their children (1 point), to consult endocrinologist (1 point), thyroid pro ile tests and their interpretation with hypothyroidism (1 point), foods need to avoid in hypothyroidism (1 point), treatment option in hypothyroidism (1 point), dose titration requirement in pregnant women (1 point) different brands of thyroid tablets does not show similar effect (1 point), lifelong usage of thyroid tablets (1 point), drugs not to be taken with thyroid tablet (1 point), and complications of under or no treatment of hypothyroidism (1 point). After determination of knowledge points, original Blooms Cut Off Points were used to categorize knowledge levels, where 80-100% correct responses contain a score of (13-16) meant a good knowledge, 60-79% correct responses comprise a score of (10-12) meant a moderate knowledge and <60% correct responses comprise a score of (9 or less than 9) meant a poor knowledge (Narayana et al, 2017)…”
Section: Assessment Of Knowledge Towards Hypothyroidism and Its Managmentioning
confidence: 99%
“…Cancer is a major public health problem and one of the leading causes of death in the world today 14 . Cervical cancer is the second most common cancer among women worldwide 15,16 . One third of newly diagnosed cancers among women in the India are cervical cancers and that is for the infection with some types of HPV (Human Papilloma Virus).…”
Section: Introductionmentioning
confidence: 99%